2017
DOI: 10.22266/ijies2017.1031.12
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Fruit Fly Optimization Algorithm for QoS Aware Cloud Service Composition

Abstract: An improved fruit fly optimization algorithm based on discrete immune optimization is proposed for quality of service (QoS) aware cloud service composition. The selection and composition of cloud services based on QoS criteria is formulated as NP hard optimization problem. We determined pareto optimal service set which is nondominated solution set as input to the improved fruit fly optimization algorithm. A mathematical model is derived to enhance local search capabilities and also improves the fitness value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…As opposed to that, economic frameworks are described as "theoretical constructs that characterize economic processes by a collection of variables and a set of logical and quantitative linkages between them". The composition of cloud services challenge is seen as an optimization issue with multiple objectives to boost reaction times, cut costs, and increase throughput [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to that, economic frameworks are described as "theoretical constructs that characterize economic processes by a collection of variables and a set of logical and quantitative linkages between them". The composition of cloud services challenge is seen as an optimization issue with multiple objectives to boost reaction times, cut costs, and increase throughput [12].…”
Section: Methodsmentioning
confidence: 99%
“…There are more research concerns about solving the problem of selecting the most appropriate services for the QoS-based cloud service composition [12], [13]. Notwithstanding, a large portion of this research focuses on static QoS values observed during composition time.…”
Section: Introductionmentioning
confidence: 99%
“…Podili et al [177] developed a hybrid BAT with a differential optimization technique. In addition, a series of work suggested the application of traditional metaheuristic, including PSO in a Mutant Beetle Swarm [178], the discrete immune algorithm in a fruit fly optimization [179], and gravi-tational attraction search embodiment in traditional imperialist competitive algorithm [180] in order to exploit advantages of both methods in a unified hybrid solution. Furthermore, Chifu et al [181] proposed a honey-bees mating optimization algorithm with a fusion of components from the genetics algorithm, tabu search, and reinforcement learning.…”
Section: Classification Of Hybrid Metaheuristicmentioning
confidence: 99%
“…In this paper, the focus is on QoS-aware WSC approaches based on GA only. Hence other optimization approaches such as fruit fly optimization [13] are not taken into consideration in this section. Also approaches that cover WSC in geodistributed cloud environment [14] are not taken into consideration in this section too.…”
Section: Related Workmentioning
confidence: 99%